THE EXISTENCE AND POWER OF “NINIAK MAMAK” IN PRESERVING THE LUAMBEK DANCE WITHIN THE SINTUAK COMMUNITY: KEBERADAAN DAN KEKUASAAN NINIAK MAMAK DALAM MEMBUDAYAKAN TARI LUAMBEK PADA MASYAKARAT SINTUAK - Darmawati Darmawati (LLDIKTI Wilayah X, 2021)
Niniak Mamak is part of a social group within Minangkabau tribe. He acts as a customary leader in Minangkabau clan. Niniak Mamak plays an important role in sustaining and continuity of cultures and customs which exist in the village. Thus, the role of Niniak Mamak becomes important in socio-cultural life of Minangkabau community. This article describes the role of Niniak Mamak in maintaining Luambek art in Sintuak village, Padang Pariaman district. The role and efforts of Niniak Mamak with his power as tribal leaders is the focus of attention in this study. This study is a qualitative research using descriptive analysis method. Qualitative data were obtained through literature study, direct observation, and various interviews with informants. Interviews and observations were based on indicators designed to refer to research questions. The analysis was carried out by combining the ethnographic and phenomenological analysis model as well as referring to the Miles and Huberman model. The result shows that the existence of Niniak Mamak with his power as rulers of relatives can encourage nephews and people in the community to be involved in preserving Luambek dance and cultivate it as a cultural heritage of their ancestors. In addition, through his role as a customary leader, Niniak Mamak places Luambek art as a symbol of his greatness in Sintuak community, Padang Pariaman district.